Isolated Native Tricuspid Valve Endocarditis in a Nonintravenous Drug User. (23rd November 2020) - Shibru, Habtewold; Greffie, Ermias shenkutie; Abay, Zenahbezu; Muhie, Oumer Abdu
Abstract : Infective endocarditis (IE) is a disease characterized by high morbidity and mortality. IE was first described in the mid-16th century. Right-sided infective endocarditis (RSIE) represents 5% to 10% of all IE episodes in adults. RSIE can be divided into three groups according to the underlying risk factors: intravenous drug users (IDUs), cardiac device carriers, and the "three noes" group (no left-sided IE, no IDUs, and no cardiac devices). Tricuspid valve endocarditis in nonintravenous drug users can occur in a variety of conditions including congenital heart disease, intracardiac devices, central venous catheters, and immunologically debilitated patients. Due to the rareness of isolated native nonrheumatic tricuspid valve endocarditis, here, we like to present an 18-year-old male from rural Ethiopia with the diagnosis of isolated native tricuspid valve endocarditis that was treated and cured.